2019
DOI: 10.1111/grow.12291
|View full text |Cite
|
Sign up to set email alerts
|

Diverse diversities—Open innovation in small towns and rural areas

Abstract: It is generally accepted that cities and other forms of geographic agglomerations are conducive to innovation because their density and variety of firms, sectors and individuals create a diverse environment. However, a growing body of work shows that innovation also occurs in peripheral regions and small towns. Furthermore, work on rural social networks shows that diversity is multidimensional, and that along certain dimensions networks developed in rural areas are more diverse than those observed in cities. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 56 publications
(163 reference statements)
3
47
0
2
Order By: Relevance
“…The findings also have implications for mainstream economic geography. In line with recent research (Fitjar & Rodríguez‐Pose, ; Grillitsch & Nilsson, , ; Isaksen, ; Meili & Shearmur, ; Shearmur & Doloreux, ), this paper has shown that innovation studies must overcome their predominant focus on core regions to also include conceptual and empirical work on innovation in peripheral regions. Furthermore, these findings contribute to the policy debate, as they dismiss the dominant unfavourable view on peripheral locations.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The findings also have implications for mainstream economic geography. In line with recent research (Fitjar & Rodríguez‐Pose, ; Grillitsch & Nilsson, , ; Isaksen, ; Meili & Shearmur, ; Shearmur & Doloreux, ), this paper has shown that innovation studies must overcome their predominant focus on core regions to also include conceptual and empirical work on innovation in peripheral regions. Furthermore, these findings contribute to the policy debate, as they dismiss the dominant unfavourable view on peripheral locations.…”
Section: Discussionsupporting
confidence: 75%
“…As these firms provide employment for highly skilled workers, they might contribute to halting brain drain and to even attract talent from outside the region (Meili & Shearmur, 2019). Recent theoretical advances like the peripheralisation approach have also highlighted that geographical remoteness is not a sufficient factor for delimiting peripheral regions.…”
Section: Eder and Tripplmentioning
confidence: 99%
“…Overall, while it is important to acknowledge the understanding of development in Steinbach and Winkler provided by previous research, it is also worth stating that the overall analysis of the standardized firm responses appears to show that many currently accepted bases of business expansion have limited utility in this study. In addition, these findings (and others to be discussed) confirm earlier findings on the uniqueness of small city development strategies and trajectories (see Meili & Shearmur, 2019; van Heur, 2010).…”
Section: Nearby Suppliers 3 27supporting
confidence: 89%
“…In many ways, the most dynamic small cities provide a rich set of examples of how each has built upon unique, location-based characteristics to foster a setting in which growth can occur (Waitt & Gibson, 2009). Given all of this, it is clear that more attention to small cities is needed, especially research that acknowledges the unique development trajectories connected to small city success stories (Amin & Graham, 1997;Meili & Shearmur, 2019;van Heur, 2010). On balance, a reasonable basis for proceeding is to acknowledge that when small cities do succeed, they often succeed differently from larger centers (Robinson, 2002(Robinson, , 2006 and that their success generates highly positive and meaningful impacts for their regions (Dijkstra et al, 2013).…”
Section: Small Cities and Their Developmental Pathsmentioning
confidence: 99%
See 1 more Smart Citation